Physical condition, psychological status, and posttraumatic stress disorder among recovered COVID-19 subjects: A mediation analysis - Zhou, Kai; Chi, Hongbo; Wang, Jing; Zheng, Yufen; Pan, Juan; Yu, Die; Xu, Jiaqin; Zhu, Hongguo; Li, Jun; Chen, Shiyong; Zhao, Xinzhuan; Wu, Xiaomai; et al. (Frontiers in Psychiatry, 2022)
The physical condition of individuals who contracted COVID-19 had a profound influence on mitigating the physical and psychological impact of the disease and the symptoms of posttraumatic stress disorder (PTSD). Little attention has been focused on the influence of physical condition on PTSD among recovered COVID-19 subjects. This study explored the relationship between physical and psychological status and PTSD and the potential mechanisms. Questionnaires were completed by 73 (50.7%, 73/144) COVID-19 recovered subjects who were diagnosed in Taizhou, Zhejiang, China. We conducted a face-to-face survey from January 17 to March 10, 2020. The mediation analysis approach was applied in this research. Our data show that recovered COVID-19 subjects who were in better physical condition exhibited fewer psychological problems (B [95%CI], -1.65 [-3.04, -0.26]) and lower PTSD (B [95%CI], -6.13 [-9.43, -2.83]). In addition, the worse the psychological status of recovered COVID-19 subjects was, the stronger the PTSD (B [95%CI], 0.58 [0.02, 1.14]). Moreover, psychological status could significantly mediate the impact of physical condition on PTSD(〖β_1 θ〗_2=-0.87). Together, COVID-19 recovered subjects who have better physical condition could decrease their PTSD, and the worse the physical condition of COVID-19 recovered subjects would increase their psychological problems. Our finding about psychological status could significantly mediate the impact of the physical condition on PTSD might be useful for medical institutions and the government seeking to help with the follow-up rehabilitation training of recovered COVID-19 subjects.